HUBUNGAN SISTEM PEMBELAJARAN DARING DENGAN TINGKAT STRES MAHASISWA FAKULTAS KEPERAWATAN SEMESTER 7 UNIVERSITAS PEMBANGUNAN INDONESIA MANADO DI ERA COVID-19 - Kukus, Arisanti (Journal Of Community & Emergency, 2024)
The online learning system is one of the government’s alternative efforts in carrying out learning activities in the midst of the current pandemic situation, where learning is carried out using internet media. Stress in general is the body’s response to any existing stimulus or pressure. The aim is to find out whether there is a relationship between the online learning system and the stress level of 7th semester nursing students at Universitas Pembangunan Indonesia Manado in the Covid-19 Era. This study uses a quantitative descriptive design using a cross sectional study with a sample of 56 respondents taken using a purposive sampling method. Based on research conducted from 56 (100%) respondents, 32 respondents (57.1%) stated that the online learning system was ineffective and 24 respondents (42.9%). The results of research conducted from 56 (100%) respondents with mild stress levels as many as 12 respondents (21.4%) moderate stress levels 14 respondents (25.0%) and severe stress levels 18 respondents (32.1%), stress levels very heavy amounted to 12 respondents (21.4%). Based on the results of statistical tests using Person Chi Square , the p value = 0.001 (α < 0.05) Ha is accepted, then there is a relationship between the online learning system and the stress level of 7th semester nursing students, Universitas Pembangunan Indonesia Manado in the Covid-19 Era. The conclusion of this study shows that there is a "Relationship between the Online Learning System and the Stress Level of Semester 7 Nursing Students at the Indonesian Development University Manado in the Covid-19 Era".